THE INFLUENCE OF BRANCHES IN THE PERFORMANCE OF POWER-LINE COMMUNICATION SYSTEMS THAT USE MC-CDMA WITH REED SOLOMON CODING - Felix, Emmanuel; Anatory, Justinian; Kissaka, Mussa M (Tanzania Journal of Engineering and Technology, 2017)
Power-line network is proposed as an infrastructure for Information and Communications Technologies (ICTs) services provision. However, there are a number of factors that contribute greatly to power-line communication performance degradation. These include number of branches that can be added or removed from the power- line network, lengths of the branch lines, loading etc. It has been pointed out that the number of branches is one of the factors that affects power-line performance to a certain extent. In this paper the influence of number of branches on the performance of Broadband Power-line communication (BPLC) that uses MC- CDMA modulation scheme with Reed Solomon coding is investigated. It is shown that with substantial number of branches at a particular node in power-line a performance BER of 10-6 at SNR of about 25dB with channel capacity of 300Mb/s can be attained